Analytical characterization of Baltic amber and pottery - Kareiva, Aivaras; Kiuberis, Jonas; Merkevičius, Algimantas (Archaeologia Lituana, 2011)
Amber is the most numerous group of archaeological finds and its analysis reveals important information about the daily life and the ethnical and cultural aspects of the society of the period (Kaiserling, 2001, p. 285; Zompro, 2005, p. 251). The National Museums located all over the world contain thousands pieces of amber in its collections. These important amber objects in museums and archives sometimes suffer very serious damage (Waddington, 1988, p. 25; Williams, 1990, p. 65; Thickett, 1995, p. 217). [...]